Case Series: COVID-19 in African American Patients With Sarcoidosis - Manansala, Michael; Ascoli, Christian; Alburquerque, Ana Goico; Perkins, David; Mirsaedi, Mehdi; Finn, Patricia; Sweiss, Nadera J. (Frontiers in Medicine, 2020)
Data on the clinical presentation and outcomes of sarcoidosis patients with COVID-19 is scarce. In this case series, we identifed 5 out of 238 sarcoidosis patients that are enrolled in an ongoing longitudinal observational study who developed COVID-19 during the study period and follow their clinical course. 4 patients recovered completely while one expired during hospital admission. Our preliminary experience suggests that African American patients with chronic sarcoidosis treated with DMARDS or anti-TNF therapy do not seem to be at increased risk of respiratory or life-threatening complications from SARS-CoV-2 compared with the general population, although at the present time, we advocate for maintaining a high level of vigilance and strict follow-up in this patient population.